Consciencia ecológica y desarrollo urbano: Reserva Thomas Van Der Hammen (2017)
The project of investigation " ecological Conscience and urban development " is developed environment to the Reservation Thomas Van Der Hammen, who nowadays is immersed in a great political polemic, where on the one hand, the current administration is projecting the Reservation as a future urbanized zone, which will be affecting the environment, that different environmentalists, allied groups and national identities international eh, are looking for the protection and restoration of the same one. Car's declaration decided that it would remain as Reservation, giving period in years in order that uses that go in opposition to the protection of the environmental resources, it could be located in another side, out of the zone limited as Reservation.